Co-Ce Clay-Based Materials: Their Feasibility as Catalysts for Soot and CO Oxidation Reactions - Courtalón, Natalia Lorena (2024)
A series of Co-Ce clay-based catalysts were prepared via the wet impregnation method and tested for the catalytic combustion of diesel soot and carbon monoxide. The objective of this work was to find a suitable catalyst with an optimized active phase composition in order to structure this system using a 3D-printing technique. The physicochemical characterization indicated that the support was mainly composed of kaolinite and quartz. When supported on commercial clay, the mixture of oxides (Co3O4 spinel and CeO2 fluorite) had higher activity than the individual oxides. The formation of a solid Co-Ce solution was verified along with a synergistic effect between these two selected metal oxides. The optimal molar composition was Co:Ce = 90:10. The corresponding catalyst showed the highest catalytic activity for soot combustion, with 335 ◦C being the temperature of the maximum combustion rate. Also, it produced the best system for CO oxidation. This formulation showed a balanced proportion of Co3+ and Co2+ on the surface and had the highest content of Ce3+ surface species among the catalysts prepared, which played a key role in the oxidation reactions studied.